Controllable Growth of Aligned Monocrystalline CsPbBr3 Microwire Arrays for Piezoelectric‐Induced Dynamic Modulation of Single‐Mode Lasing. Issue 18 (25th March 2019) - Yang, Zheng; Lu, Junfeng; ZhuGe, Minghua; Cheng, Yang; Hu, Jufang; Li, Fangtao; Qiao, Shuang; Zhang, Yufei; Hu, Guofeng; Yang, Qing; Peng, Dengfeng; Liu, Kaihui; et al.
Abstract: CsPbBr3 shows great potential in laser applications due to its superior optoelectronic characteristics. The growth of CsPbBr3 wire arrays with well‐controlled sizes and locations is beneficial for cost‐effective and largely scalable integration into on‐chip devices. Besides, dynamic modulation of perovskite lasers is vital for practical applications. Here, monocrystalline CsPbBr3 microwire (MW) arrays with tunable widths, lengths, and locations are successfully synthesized. These MWs could serve as high‐quality whispering‐gallery‐mode lasers with high quality factors (>1500), low thresholds (<3 µJ cm −2 ), and long stability (>2 h). An increase of the width results in an increase of the laser quality and the resonant mode number. The dynamic modulation of lasing modes is achieved by a piezoelectric polarization‐induced refractive index change. Single‐mode lasing can be obtained by applying strain to CsPbBr3 MWs with widths between 2.3 and 3.5 µm, and the mode positions can be modulated dynamically up to ≈9 nm by changing the applied strain. Piezoelectric‐induced dynamic modulation of single‐mode lasing is convenient and repeatable. This method opens new horizons in understanding and utilizing the piezoelectric properties of lead halide perovskites in lasing applications and shows potential in other applications, such as on‐chip strain sensing. Abstract : CsPbBr3 shows great potential in laser applications due to its superior opto‐electronic characteristics and stability. The growth of CsPbBr3 wire arrays with well‐controlled sizes and locations is beneficial for cost‐effective and largely scalable integration into on‐chip devices. In addition, dynamic modulation of perovskite lasers is vital for practical applications.